How can we include disability issues in undergraduate curricula at the University of Cape Town? - Nwanze, Ikechukwu (Department of Health and Rehabilitation Sciences, 2017)
This study examined how disability issues can be included into the undergraduate curriculum at the University of Cape Town (UCT). It was based on Ohajunwa's (2012) study which looked at whether disability is included at all in UCT curricula. She found that disability issues were included but with minimal support and was done through individual effort and not a university collective effort. She also found that lecturers did not have support structures on how to even begin to think of including disability issues. This study therefore asked how disability issues can actually be included in the undergraduate curriculum at UCT. A literature search found that institutions in South Africa have not started looking at the inclusion of disability issues in the curriculum in universities but rather have been focusing on the inclusion of students with disabilities. Inclusion of disability issues in university curricula has been happening on a small scale internationally with institutions citing a lack of support on how this can be embedded into all curricula rather than as an add-on. The aims and objectives of this study, therefore, were to identify what content area should be the focus for the inclusion of disability issues, what teaching and assessment methods should be used, and what support structures are likely to be needed. The methodology used was a case study design and the case of disability inclusion in the University of Cape Town undergraduate curriculum. Focus group discussions, in-depth interviews, document analysis, and a reflective journal were means of data collection. Data were analysed using a thematic analysis method with an inductive approach. The findings are reported in relation to a curriculum process framework which emphasises the links between why disability issues should be included, how, when and by what means. The findings are presented in four themes: 1. Achieving transformation through curriculum change; 2. Build and design the curriculum for diversity; 3. Creating a community of practice; and 4. Translating talk into action. Trustworthiness and rigor were observed through member checking for credibility, reflexivity and peer-review for confirmability, and an audit trail for dependability. The study concluded with a recommendation that with the use of the curriculum process framework that emerged from the study, disciplines may have a way to include disability issues in undergraduate curricula in order to transform these curricula. However, this should be done in an integrated way through considering various parts of the curriculum process framework.